HUBUNGAN SIKAP IBU DALAM PENGELOLAAN SAMPAH DENGAN VOLUME SAMPAH ORGANIK DI GANG PANCASILA LUBUK PAKAM - Delita Br Panjaitan; Anggi Isnani Parinduri; Irmayani Irmayani (JURNAL KESMAS DAN GIZI (JKG), 2020)
The problem of waste management is currently still a problem that is difficult to do, where the limited land for the disposal of waste, a careless attitude makes the volume of waste high. The purpose of this study was to analyze the relationship between attitudes towards waste and the volume of organic waste in the Pancasila alley. This research uses analytical research with cross sectional study and uses Chi Square. The sample in this study were 40 respondents and were taken by total sampling. Primary data was collected by means of a questionnaire and for the volume of waste, it was carried out by direct measurement. This research was conducted in the pencasila alley. Based on the attitude of the respondents, there were 13 respondents with good attitudes (32.5%) and 27 respondents with poor attitudes (67.5%). There is a relationship between attitude and volume of waste (p = 0.001). The community needs to raise awareness about the management of waste produced by each household.